"DIGITAL UZBEKISTAN - 2030" PROGRAM'S MAIN DIRECTIONS AND ANALYSIS OF THE ROLE OF ARTIFICIAL INTELLIGENCE - Sodikova Nigora Shukhrat kizi (Innovate Conferences, 2025)
This article examines the main directions and the role of artificial intelligence (AI) within the framework of the “Digital Uzbekistan – 2030” program aimed at implementing the digital transformation of the Republic of Uzbekistan. The article aims to analyze the prospects and impact of Artificial Intelligence in various fields, in particular, in public administration, economy and education. It also identifies the strategies of the program on artificial intelligence technologies and the opportunities and urgent tasks that will contribute to their socio-economic development. The article examines the impact of Artificial Intelligence on the digital transformation in Uzbekistan and the role of government.
Keywords: Digital Uzbekistan, artificial intelligence, digital transformation, public administration, economy, education, cybersecurity, digital economy, 2030 strategy.